Keberkesanan, Corak Rantaian Komunikasi Dan Kedinamikan Pasukan Maya Dalam Organisasi Bertaraf Koridor Raya Multimedia (Msc) Terpilih - Aripin, Norizah (2013)
These days teamwork plays an important role in the organisation due to the effects of globalisation in the world of commerce. Although communication technologies help simplify the management of work in virtual teams, there still exists many problems such as interpersonal communication and team relationships when working with other members based in different locations and time zones. Therefore, this study was undertaken to understand how virtual teams work within the constraints of distance and time. Epistemological paradigm positivist (quantitative) and interpretivist (qualitative) approaches were utilised in this study to obtain a general description of the effectiveness of virtual teams, and network communication patterns besides a better understanding of the dynamics of virtual teams. A total of 363 respondents, and three different types of virtual teams were involved in this study. This involved staff participation among those with experience in virtual team working conditions based at an MSC status organisation. Results of the study found four factors that contribute to virtual team effectiveness. They are internal dynamics of the team in terms of frequency of use of communication media (fax, e-mail and shared database systems), the internal dynamics of the team in terms of team relationships (relationship among team members, relationship and level of trust among leaders with team members), diverse work practices and team recognition.